Administering a SQL database infrastructure exam 70-764 certification training : prepare for the Microsoft 70-764 exam and work towards your MCSA: SQL 2016 database administration certification - Long, Mark (O'Reilly, 2017)
"The course prepares you to take Microsoft exam 70-764, the first of two tests you must pass in order to earn the Microsoft Certified Solutions Associate (MCSA): SQL 2016 Database Administration certification. Passing the 70-764 exam indicates to the world that you have what it takes to administer the SQL database infrastructure."--Resource description page.